2021
DOI: 10.1016/j.ctrv.2021.102238
|View full text |Cite
|
Sign up to set email alerts
|

NRAS mutant melanoma: Towards better therapies

Abstract: Genetic alterations affecting RAS proteins are commonly found in human cancers. Roughly a fourth of melanoma patients carry activating NRAS mutations, rendering this malignancy particularly challenging to treat. Although the development of targeted as well as immunotherapies led to a substantial improvement in the overall survival of non-NRAS mut melanoma patients (e.g. BRAF mut ), patients with NRAS mut melanomas have an overall poorer prognosis due to the high aggressiveness of RAS mut tumors, lack of effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 139 publications
0
67
0
Order By: Relevance
“…The mutations of NRAS usually occur at G12, G13, and Q61 sites, and are found in around 25% of cases of melanomas. 32 Compared to BRAF V600E mutation which can be effectively targeted by some agents like vemurafenib and dabrafenib, therapeutic options for melanoma harboring NRAS mutations lag behind. A recent study has identified STK19 as a novel NRAS activator by enhancing its phosphorylation and binding to downstream effectors.…”
Section: Signal Pathways Driving Melanoma Pathogenesismentioning
confidence: 99%
“…The mutations of NRAS usually occur at G12, G13, and Q61 sites, and are found in around 25% of cases of melanomas. 32 Compared to BRAF V600E mutation which can be effectively targeted by some agents like vemurafenib and dabrafenib, therapeutic options for melanoma harboring NRAS mutations lag behind. A recent study has identified STK19 as a novel NRAS activator by enhancing its phosphorylation and binding to downstream effectors.…”
Section: Signal Pathways Driving Melanoma Pathogenesismentioning
confidence: 99%
“…NRAS-mutant melanoma is more invasive, resulting in a lower median OS time and lagging treatment options. [29][30][31] Our results showed that the NRAS mutation rate of the OG was higher than that of the YG, but the specific mechanism needs to be further explored. In addition, the upregulated genes in the YG were mainly enriched in the immune response and immunotherapy pathways, while those in the OG were mainly enriched in aging-related pathways such as cell and epidermal development and differentiation.…”
Section: Discussionmentioning
confidence: 80%
“…To avoid rereviewing the topics which were covered, we refer the reader to these recent excellent publications. These include subcellular localization and considering exploiting the membrane in therapeutics (Kattan and Hancock 2020;Zhou et al 2018), mutational analysis and isoform signaling (Li et al 2018a;Munoz-Maldonado et al 2019;Prior et al 2020;Randic et al 2021), subcellular localization and tumor growth (Garcia-Ibanez et al 2020), Ras-ERK signaling (Zaballos et al 2019) and MAPK inhibition (Heppner and Eck 2021;Ullah et al 2021), isoform-specific differences in the effector binding regions (Nakhaeizadeh et al 2016), and the recent contributions from the Mark Philips lab on KRas4A reversible palmitoylation and colocalization (Amendola et al 2019) and on membrane association/colocalization (Zhou et al 2020). Isoform signaling specificity at the membrane (Nussinov et al 2018a), KRas mobility in the membrane (Nussinov et al 2019b) and nanoclustering (Nussinov et al 2019a) were also reviewed as well as genetic aspects of KRas signaling networks (Jinesh et al 2018).…”
Section: Earlier Discussion On Ras Isoformsmentioning
confidence: 99%